Pengembangan Modul Reaksi Reduksi dan Oksidasi Berbasis Pendekatan Saintifik dengan Menerapkan Teknik Probing dan Prompting untuk Pembelajaran Kimia Kelas X SMA/MA - Vivi Olivia Susanti, Ellizar, Andromeda (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Curriculum 2013 asked students to be active to construct their knowledge. The one way tomaked students to be active by asking questions. It can be integrated into the module. This researchaimed to get the scientific approach-based module using probing and propmting technicson reduction and oxidation reaction lesson and to showed the validity level and practicalityfrom module. This research utilized research and development (R&D) research which is used toget a product. The model of development used in this research is Plomp model, consist of (1)preliminary research, (2) prototyping stage, (3) assessment phase. The developed module is validatedby five validator and carried out practicality test by six students was small group evaluationand thirty students was field test at eleven grade of science at Senior High School 12 Padang.This research uses instrument, and questionnaire in which consisted of validity and practicalitysheets. Then, technic of data collection through questionnaire, “momen kappa”. thatreduction and oxidation reaction has high validity, (0.81) with a level of validity is very highand small group practicality is 0,87. Field test has been practicality 0.86 by students and 0.82by teachers with a level practicality was very high.Keywords : Module, scientific apporoach, probing and prompting techniqs, reduction and oxidationreaction, Plomp model